2019
DOI: 10.1590/s1517-707620190003.0709
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ti-35Nb alloy surface modified by controlled chemical oxidation for surgical implant applications

Abstract: Titanium-Niobium alloys have been studied for biomedical applications due to their satisfactory biocompatibility. In order to improve the long-term implantation, surface modification techniques have been developed to generate suitable topography, roughness, chemical composition, surface energy, etc. Considering this approach, the present work aimed to characterize Titanium-35Niobium (Ti-35Nb) surface modified by controlled chemical oxidation. Ti-35Nb (wt%) substrates were processed by powder metallurgy. The po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
6
0
2
Order By: Relevance
“…In titanium alloys, Ti-27Nb has attracted attention as a promising material for bone implants because of high fatigue strength, non-corrosiveness, non-toxicity, good mechanical properties, and superior biocompatibility [11,12]. Ti-27Nb is less ductile, having 12% less ultimate strength as compared with its counterpart Ti-6Al-4V.…”
Section: Introductionmentioning
confidence: 99%
“…In titanium alloys, Ti-27Nb has attracted attention as a promising material for bone implants because of high fatigue strength, non-corrosiveness, non-toxicity, good mechanical properties, and superior biocompatibility [11,12]. Ti-27Nb is less ductile, having 12% less ultimate strength as compared with its counterpart Ti-6Al-4V.…”
Section: Introductionmentioning
confidence: 99%
“…Alguns estudos mostram que uma forma de abaixar mais o módulo de elasticidade nas ligas de Ti é através da adição de nióbio e tântalo. Com esses elementos pode-se conseguir um módulo E ≈ 55 GPa [9][10][11].…”
Section: Características Mecânicas Do Titâniounclassified
“…Alguns trabalhos têm demonstrado que estruturas microporosas (< 20 µm) de TiO 2 produzidas na superfície do titânio e suas ligas podem favorecer a osteointegração e prevenir a falha precoce do implante. De acordo com esses trabalhos, isso ocorre devido ao espaço que esses poros proporcionam às células ósseas, o que favorece à vascularização e crescimento do tecido ósseo, levando ao travamento mecânico entre prótese e osso [11]. KOKUBO e YAMAGUCHI [15] propuseram em seu trabalho que a formação de apatita sobre o implante ocorrerá, em meio fisiológico, em função do potencial Zeta na sua superfície.…”
Section: Características Físico-químicas Do Tio2unclassified
“…Vanadium and aluminum are currently the elements most often added to titanium alloys and act as phase stabilizers [3], however, it has been shown that these elements can be harmful to human health, because the gradual release of cytotoxic elements such as aluminum (Al) and vanadium (V) pose a high risk of long-term health problems including Alzheimer's disease, osteomalacia, and other neurological conditions [4,5]. Thus, the use of niobium (Nb), a betagenic element (β-Ti phase stabilizer), has been emerging and showing great potential, as it is able to produce alloys with elastic modulus closer to the human bone and improved workability due to their body-centered cubic microstructure, in comparison to commercial pure Ti and Ti6Al4V alloy [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%